Screening for risk of cardiac death in young athletes - Rowland, T. W. (1999)
The risk of sudden cardiac death in an apparently healthy young athlete is extraordinarily small. Approximately 10-13 such cases are reported annually in the United States. Even assuming this represents under-reporting, the chance of such a tragedy in a given athlete is probably less than 1:250,000. Four cardiovascular abnormalities account for the great majority of reported cases of sudden cardiac death in young athletes: hypertrophic cardiomyopathy (a pathologically enlarged heart), congenital (inherited) abnormalities of the coronary arteries, dissecting aortic aneurysms (bulging of the aorta with blood passing between layers of the arterial wall) in athletes with Marfan syndrome (a congenital disorder of connective tissue), and congenital stenosis (narrowing) of the heart valve leading to the aorta. Routine physical examination during the pre-season medical evaluation can detect those with Marfan syndrome and aortic stenosis, and athletes with hypertrophic cardiomyopathy and coronary artery abnormalities may give a history of chest pain or fainting with exercise. Athletes with the latter two conditions, however, often go undetected. Additional diagnostic procedures such as echocardiography and electrocardiography are not recommended for routine screening of athletes because the techniques are not cost-effective and have a high rate of false positive findings. Future developments, including genetic screening and the availability of defibrillators at the sport site, may decrease the incidence of sudden death. The current limitation in our ability to identify athletes at risk necessitates acceptance that participation in sports carries some risk.